Socio-Environmental and Behavioral Correlates of Having Ever Had Sexual Intercourse Among Adolescents in Peru: A School-Based Cross-Sectional Study. Issue 2 (3rd April 2017) - Sharma, Bimala; Nam, Eun Woo; Kim, Ha Yun; Kim, Jong Koo; Vasquez Paja, Doris Jackeline
ABSTRACT: Objective : We assessed the socio-environmental and behavioral correlates of having ever had sexual intercourse among Peruvian adolescents aged 12–18 years in Lima. Methods : A cross-sectional study was conducted in 2014. Result : Of 950 participants, 26.5% of males and 13.0% of females had ever had sexual intercourse. Early adolescents who ever had sexual intercourse had higher odds of being insulted, being involved in a fight, and smoking; whereas late adolescents having sexual experiences were more likely to be male and to report smoking, alcohol consumption, involvment in a fight, and having no/low parental understanding. Conclusion : An integrated approach is useful in addressing risk behaviors in adolescents.